733 Integrative molecular profiling of high-grade primary prostate cancer identifies patients with a biomarker profile that favors the combination of standard of care (SOC) therapy with immunotherapy. (10th December 2020) - Gjini, Evisa; Trillo-Tinoco, Jimena; Browne, Andrew; Powles, Ryan; Wang, Tai; Tauras, Christine; Lako, Ana; Ferrer-Luna, Ruben; Bleicher, Zoe; Consedine, Timothy; Zhou, Chensheng; Kelemen, Evan; et al.
Abstract : Background: Prostate cancer (PCa) is primarily driven by androgen receptor (AR) signaling and has a highly immunosuppressive microenvironment. Although genomic and histopathological differences between low- and high-grade primary PCa (lgPCa and hgPCa) have been reported, an integrative assessment of multiple molecular features in the context of disease grade and metastatic outcome is lacking. We propose that a subset of hgPCa patients who relapse under SOC may benefit from adjuvant immune-checkpoint blockade (ICB) added to SOC to overcome immune suppression. Methods: We analyzed treatment naive prostatectomy tissue from a cohort of 124 primary PCa patients (n= 58, Gleason score ≤6; n= 66, Gleason score ≥ 8). We performed RNAseq expression profiling, whole-exome sequencing (WES) and immunohistochemistry. We employed digital spatial analysis in tumor vs. stromal regions to characterize differences in CD8+ T-cell topology between lgPCa and hgPCa Results: 1.Comparisons in lg vs. hgPCA: Digital spatial analysis assessing the proximity of CD8+ T-cells to tumor cells revealed a T-cell exclusion phenotype that is more prominent in hgPCa, whereas evaluation of overall CD8+ T-cell density in tumor and stromal regions did not differentiate disease grades. HgPCa had a higher frequency of at least one functional mutation in either TP53, RHPN2, or KMT2D genes compared to lgPCa. Assessment of MHC-I deficiency by IHC and mRNA revealed that hgPCa has significantly lower MHC-I protein expression compared to lgPCa. Interestingly, MHC-I loss in hgPCa associated with a T-cell exclusion phenotype. Moreover, RNAseq gene expression signatures revealed higher expression of tumor-associated macrophage (TAMs), T-regs, Cancer-Associated Fibroblasts (CAFs), DNA damage repair (DDR) genes and lower Interferon-γ (IFN- γ) expression in hgPCa compared to lgPCa. Overall, hgPCa is characterized by a combined phenotype of 'MHCIloss/IFN- γ low/CAFhigh/TAMhigh/T-reghigh/DDRhigh'. 2.Comparisons within hgPCA that develop metastasis: Unsupervised analysis of molecular features in hgPCa patients that developed metastases identified a subset of patients that exhibit a less immunosuppressive phenotype with lower tumor AR expression, retained tumor MHC-I expression, moderate CD8+ T-cell infiltration and a high IFN-γ RNA signature (figure 1 ), suggesting potential benefit from ICB therapy Conclusions: Our analysis suggests that hgPCa is characterized by low antigenicity as assessed by loss of MHC-I protein expression and an immunosuppressive microenvironment rich in CAFs, macrophages, T-regs and T-cell exclusion phenotypes. Unlike lgPCa, hgPCA can have a poor prognosis (within 5 years relapse). However, a subset of hgPCa patients that metastasized while on SOC exhibited a biomarker profile that might benefit from combination of SOC with ICB Ethics Approval: This study was approved by BMS Cambridge Massachusetts Institutional Biosafety Committee, approval number CAM_2020_12050_6 Consent: 'Written informed consent was obtained from the patient for publication of this abstract and any accompanying images. A copy of the written consent is available for review by the Editor of this journal.'